Axillary treatment for patients with early breast cancer and lymph node metastasis: systematic review protocol - Goyal, Amit; Duley, Lelia; Fakis, Apostolos (BioMed Central, 2013)
Background: For patients with early breast cancer and lymph node metastasis, axillary treatment is widely recommended. This is either surgical removal of the axillary lymph nodes, or axillary radiotherapy. The rationale for axillary treatment is that it will reduce the risk of recurrence in the axilla, and may improve survival. However, both treatments are associated with adverse effects, such as lymphedema, pain and sensory loss, and are costly to the health services and to patients. With improvements in adjuvant therapy, routine axillary treatment may no longer offer any overall advantage.